A Pragmatic Study of Diminutives in Ahmad Shawqi’s Plays - Saeed, Noura Muhammad Saleem; Kamal Hazim Hussien (Manar Elsharq Journal for Literature and Language Studies, 2023)
The present research delves into a pragmatic analysis of diminutives within Shawqi’s plays, aiming to explore the multifaceted linguistic and cultural dimensions they bring to his dramatic discourse. Diminutives, linguistic constructions that denote smallness, affection, or endearment, have long been a significant element in the Arabic language and culture, serving various communicative functions. This research aims at investigating how diminutives are strategically employed by Shawqi to convey different meanings, evoke emotional responses, and shape character interactions. The present research uses extracts taken from selected plays as data. These plays are Antra, Majnoon Layla, Qhambeez, Ameerat Al-Andalus, and Ali Bey Al-Kabir. Drawing upon the framework of pragmatics, this research analyzes diminutives in selected plays by Ahmad Shawqi. The analysis involves a qualitative approach where diminutives in Ahmad Shawqi's plays are identified through character speeches, marked on pages, documented, and categorized by the researcher using content analysis following a systematic data collection process. It examines their contextual usage, communicative effects, and cultural connotations. Through a comprehensive examination of diminutives, their forms, and their roles in dialogue, characterization, and plot development, this research seeks to derive patterns and themes that illuminate Shawqi’s unique stylistic choices and the socio-cultural factor in which his works were crafted. By approaching Ahmad Shawqi’s plays from a pragmatic perspective, this research contributes to a deeper understanding of the intricate interplay between language, culture, and dramatic artistry. The textual analysis reveals that Diminutives in Shawqi’s plays serve as strategic tools, especially in romantic situations, enhancing emotional expression and character connections. They can convey both positive and negative emotions. Diminutives enrich literary works, reflecting cultural context and societal norms. They depict social hierarchies and relationships, adding depth to character portrayals. In essence, diminutives in Shawqi’s plays are context-dependent, contributing to a deeper understanding of characters and emotions. Ultimately, this study enriches our appreciation of Shawqi’s enduring contributions to Arabic literature and his mastery of linguistic devices in shaping the theatrical experience.